Analysis of the Technology Acceptance Model (TAM) in the Acceptance of Smartboards in Elementary Schools - Aria, Ririn Restu; Apriyani, Helina; Alawiah, Enok Tuti (Vertex, 2025)
The use of Smartboards in primary school learning has become an essential part of digital transformation in Indonesian education. However, the success of this implementation strongly depends on user acceptance. This study aims to analyze the factors influencing Smartboard acceptance using the Technology Acceptance Model (TAM), which includes Perceived Usefulness (PU), Attitude Toward Using (ATU), and Intention to Use (IU). A quantitative explanatory correlational design was employed, involving primary school teachers in West Jakarta who have used Smartboards in classroom instruction. Data were analyzed using Structural Equation Modeling (SEM). The findings indicate that all indicators of PU, ATU, and IU demonstrate valid and reliable loading factor values. Structurally, PU has a positive and significant effect on IU, and ATU also shows a significant positive influence on IU. These results highlight that perceived usefulness and positive attitudes are the primary determinants shaping teachers’ intention to use Smartboard technology. The study implies that enhancing digital competencies, providing structured Smartboard training, and ensuring technical support are crucial to optimizing the implementation of Smartboard-based learning